Análise de toxicidade do metilparabeno no crescimento do Ricciocarpus natans sob diferentes concentrações e temperaturas - Sanches, Julia Romano (Universidade Federal de São Carlos, 2020)
Methylparaben is an antimicrobial preservative widely used in formulations for personal care products and cosmetics. However, this compound is not monitored at sewage treatment plants, being considered as an emerging contaminant. The modeling of the primary production of macrophyte with phytoremediation potential constitutes both a management tool and an ecological contribution to assess effectiveness of the species in decontaminating aquatic environments. In the aquatic systems, different species of macrophytes with different life forms have been used in toxicity studies. Its contamination, bioaccumulation and death show an environmental problem, since methylparaben is widely used as a preservative compound in personal care products and cosmetics. In the municipality of São Carlos - SP, methylparaben has been analyzed in water from streams, rivers, and treatment plants, in addition to studies of its toxic effect on aquatic organisms, but research on the effect of the preservative on macrophytes is still scarce. In this context, the present study aimed to evaluate the effect of four concentrations of methylparaben on the growth of the floating aquatic macrophyte Ricciocarpus natans, which were incubated at two temperatures simulating the winter/dry and summer/rainy periods. In total, 420 individuals were collected, of which 210 remained at 16ºC and 210 at 23ºC. The treatments were distributed in four concentrations of methylparaben (0.05%, 0.15%, 0.40% and 0.80%) for both temperatures. For 60 days, once a week, the length, width, and biomass of the individuals were measured. The concentrations of 0.40% and 0.80% interfered substantially in the growth once the individuals died after the third experimental week. At the 0.15% concentration, although there were differences between the growth indicators, we concluded that there was interference in the growth of individuals. However, at a concentration of 0.05%, methylparaben did not interfere with the growth of R. natans. When analyzing the temperature alone, it was found that the growth coefficient of the individuals was 15.39% higher at 23ºC (simulating the summer season). Thus, the hypothesis of this study that considered the negative effect of the presence of methylparaben in the growth medium of R. natans can be corroborated for the concentration 0.15%.
Analysis of methylparaben toxicity on Ricciocarpus natans growth under different concentrations and temperatures
Keywords: Metilparabeno; Contaminante emergente; Macrófita aquática; Methylparaben; Emerging contaminant; Aquatic macrophyte; Ricciocarpus natans; CIENCIAS BIOLOGICAS::ECOLOGIA